2014
DOI: 10.1038/npp.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed Anterior Prefrontal Control of the Mesolimbic Reward System and Increased Impulsivity in Bipolar Disorder

Abstract: Bipolar disorder (BD) is characterized by recurrent mood episodes ranging from severe depression to acute full-blown mania. Both states of this severe psychiatric disorder have been associated with alterations of reward processing in the brain. Here, we present results of a functional magnetic resonance imaging (fMRI) study on the neural correlates and functional interactions underlying reward gain processing and reward dismissal in favor of a long-term goal in bipolar patients. Sixteen medicated patients diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 49 publications
(83 reference statements)
11
63
0
Order By: Relevance
“…Given the differences between our paradigm and that of Chase et al (2013), the findings are not necessarily conflicting. However, in light of recent findings that indicate state-independent elevated striatal activity (Nusslock et al, 2014), but other researchers reporting results in the opposite direction (Trost et al, 2014), it seems to be important to separate the investigation of reward anticipation and reward outcome processing to gain a clearer picture in future studies.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the differences between our paradigm and that of Chase et al (2013), the findings are not necessarily conflicting. However, in light of recent findings that indicate state-independent elevated striatal activity (Nusslock et al, 2014), but other researchers reporting results in the opposite direction (Trost et al, 2014), it seems to be important to separate the investigation of reward anticipation and reward outcome processing to gain a clearer picture in future studies.…”
Section: Reward Processing In Ud and Bdmentioning
confidence: 99%
“…However, not all available data support this notion. Compared with HCs, individuals with BD showed elevated VS activity during hypomania (O'Sullivan et al, 2011), no differences or elevated activity in euthymic states (Caseras et al, 2013;Nusslock et al, 2012), but activity was decreased in euthymic to mildly depressed patients (Trost et al, 2014). Chase et al (2013) is the first study that examined reward feedback in BD during depressive episodes and directly compared BD and UD.…”
Section: Introductionmentioning
confidence: 99%
“…So, during the RC, subjects were forced to overcome the tendency to acquire immediate reward (reject the previously conditioned reward stimuli) in order to reach the superordinate long-term goal. This situation therefore constituted a 'desire-reason dilemma' (Diekhof et al, 2012;Diekhof and Gruber, 2010;Trost et al, 2014). For more information, see also Supplementary Figure S1.…”
Section: Experimental Procedure/drd Paradigmmentioning
confidence: 99%
“…Psychophysiological interaction (PPI) (Diekhof and Gruber, 2010;Friston et al, 1997;Trost et al, 2014) was used to assess functional interactions of the ventral striatum with prefrontal brain regions, especially the anteroventral prefrontal cortex (avPFC), in the 'DRD' situation. Previous studies using the DRD paradigm in healthy subjects had shown a significant negative functional interaction between the ventral striatum and the avPFC in the dilemma situation (Diekhof and Gruber, 2010), while this negative functional interaction had been significantly impaired in bipolar patients in our latter study comparing bipolar patients with healthy controls (Trost et al, 2014).…”
Section: Psychophysiological Interaction Analysismentioning
confidence: 99%
See 1 more Smart Citation